A Review on Security Issues and Challenges of IoT - E. Suresh Babu, Dr; Bhargav Raj, V; Manogna Devi, M; Kirthana, K (International Journal of Engineering and Technology, 2018)
This papers reviews and surveys the security issues, mechanism of internet of things (IoT) proposed in the literature. As IoT is a computing concept that describes the idea of everyday physical objects being connected to the internet and being able to identify themselves to other devices. The main advantages of IoT improve the resource utilization ratio and relationship between human and nature. In addition, it possesses various characteristics like sensing, heterogeneity, connectivity, dynamic nature and intelligence. However, it possesses several challenges like connectivity, compatibility, longevity, privacy and security. Specifically, Security and privacy are the crucial issues that need to be solved for successful deployment of IoT. Moreover, some of the data collected from the IoT are very sensitive and should not be revealed to third parties. Such data needs to be protected by some provided legislations. We reviewed some of the security challenges of IoT like secure communication, data privacy and integrity, authorizing and authenticating the devices.Â Â